The effectiveness of music therapy for the treatment of Alzheimer’s disease - Rehan, Dominka; Szydziak, Joanna; Hrapkowicz, Aleksandra; Janowska, Kinga; Szeidl, Olga; Wołoszczak, Julia; Wołoszczak, Julia; Mioskowska, Agnieszka; Dąbkowska, Daria (Journal of Education, Health and Sport, 2024)
Introduction: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and the most prevalent cause of dementia. It is caused by the degeneration of brain cells due to the accumulation of intracellular hyperphosphorylated tau - containing neurofibrillary tangles and extracellular plaques of amyloid-beta peptide. While pharmacotherapy remains the main form of treatment (including cholinesterase inhibitors and antagonists to NMDA), various non-pharmacological therapy modalities have gained increasing attention as complementary treatment options, such as music therapy. Purpose of the study: This review examines the role of music therapy as an important complement to baseline therapy for AD patients, focusing on indications, methods, and the prospect of music therapy. Materials and methods: A comprehensive literature review was conducted, analyzing 48 studies from the PubMed database (English-language, up to November 2024) that assess the efficacy, methods, and prospect of music therapy as an adjunctive therapy in Alzheimer’s disease. Conclusions: Music therapy is an established and effective supportive treatment for AD patients. It has demonstrated clinical success over many years as a tool for engaging multiple motor and sensory areas, shaping emotions, and evoking memories. This may be due to activating limbic and paralimbic structures, enhancing neuroplasticity, and modulating neurotransmitter systems. Despite the observable benefits of music therapy, the methodological limitations of existing studies highlight the need for further long-term research to standardize treatment approaches.